A Technical Study of Tennis Forehand Topspin Based on Sports Mechanics - Huang, Tian; Gao, Jinxia (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Forehand topspin is an important technique in tennis.OBJECTIVES: This paper studied the forehand topspin through sports mechanics to understand the technical feature differences of tennis players with different levels and to provide a reference for guiding the movement of forehand topspin of tennis players.METHODS: They were divided into groups A and B. Group A included the first-grade players, and group B included the second-grade players. The forehand topspin movement of the players was filmed by two high-speed cameras. The videos were processed using APAS software. The results showed that the ball speed of group A was 47.89 ± 5.64 m/s, which was significantly higher than that of group B (p < 0.05, i.e., significant level). After the back swing, group A had significantly smaller lower limb joint angles than group B (p < 0.05) and larger upper limb joint angles and velocities than group B. At the moment of swinging to hit the ball, the right elbow joint angle was smaller and the upper limb joint velocitywas faster in group A. At the end of the follow-through, group A had smaller right shoulder and elbow joint angles than group B (p < 0.05).RESULTS: The experimental results show the difference between players with different levels.CONCLUSION: Higher level players have more adequate lower limb pedaling and stretching and upper limb stretching and higher limb swing speed so that they can hit better topspin shots.
Keywords: tennis; sports mechanics; topspin; shoulder joint; lower limb; ball speed